Organizational Change Management and Innovation as a Performance Improvement Strategy in the Industrial Transformation Era 4.0 - Vika Fransisca (Al-Makki Publisher, 2025)
The Fourth Industrial Revolution has fundamentally changed the global business landscape, forcing organizations to adapt quickly through digital transformation. However, 60–70% of digital transformation projects fail due to weak change management practices, so a comprehensive framework that integrates change management, organizational innovation, and performance in the context of Industry 4.0 is needed. This research aims to develop and test a model that explains how organizational change management and innovation function as a performance improvement strategy during the transformation of Industry 4.0, by examining the mediating role of organizational innovation and identifying the key dimensions of change management (human, organizational, technical, and leadership factors). The research design used an explanatory quantitative approach with 300 respondents from manufacturing and service companies in Indonesia who have applied Industry 4.0 technology. Data was collected through a 7-point Likert scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The results showed that change management had a significant effect on innovation (? = 0.685, p < 0.001) and performance (? = 0.312, p < 0.001), while organizational innovation was also significant on performance (? = 0.524, p < 0.001). The model explains 46.9% innovation variance and 67.3% performance with partial mediation (VAF = 53.5%).